Ovarian Development of House Fly (Musca domestica L.) (Diptera: Muscidae) - Xider, Karim Mohammed; M. Amin, Havall (Kurdistan Journal of Applied Research, 2018)
The ovarian development of Musca domestica, was examined under light microscope. There are two ovaries in the adult female of fly. Each ovary was formed of about 60-70 polytrophic ovarioles. The ovariole in cross sections organized in several circles. From cytological observations, ovary development and oogenesis could be divided in to 6 stages; ovaries with no noticeable follicle cells existing were characterized as (stage1), the follicle-growing stages considered as (stage2, 3), the vitellogenen in stages (stages4, 5(and mature egg stage (stage6). The oocyte initiated development at first stages of oogenesis; the nurse cells and follicle epithelial cells were considered to fulfill important functions with regard to the growth of the oocyte.